(untitled) (Research, Society and Development, 2022)
Leishmaniasis is an infectious-parasitic disease caused by intracellular protozoa of the genus Leishmania sp. It presents in two classical forms, cutaneous leishmaniasis (CL) and mucosal leishmaniasis (ML). The diversity in clinical forms found in ATL is due to the interaction of the Leishmania species involved in the infection, the immune response of each individual against the parasite and even the vector. Of the host defense components important for the elimination of Leishmania sp., we can highlight the adaptive immune response, which is fluently mediated by cells. It is known that disease resistance or susceptibility is related to the level of expansion and differentiation in effector cell subpopulations, where CD4+ T cells can differentiate into Th1, or Th2 type T cells. This project aimed to evaluate the lymphoproliferation profile of peripheral blood mononuclear cells (PBMC) from patients with CL and from healthy individuals sensitized by soluble antigens of Leishmania (V.) guyanensis, in order to understand the cell modulation induced by this species, the etiologic agent of ATL prevalent in the Amazon region. The lymphoproliferative response was evaluated in cell culture stimulated with soluble L. guyanenesis antigen and Phytohemagglutinin - PHA (10 g/mL) using the BrdU Cell Proliferation ELISA Kit. The results showed that all individuals showed lymphoproliferation in response to the mitogen. Regarding the antigen, the patients before and after treatment, showed a high lymphoproliferative response. Thus, we can suggest that there was T lymphocyte expansion in vitro in the primoinfected groups and after treatment.